Performance, Exile and ‘America’
XIII, 266 p. 11 illus.
Keywords: This collection investigates dramatic and performative renderings of 'America' as an exilic place particularly focusing on issues of language, space and identity. It looks at ways in which immigrants and outsiders are embodied in American theatre practice and explores ways in which 'America' is staged and dramatized by immigrants and foreigners.